Keberhasilan IB menggunakan semen beku hasil sexing dengan metode sentrifugasi gradien densitas percoll (SGDP) pada sapi Peranakan Ongole (PO) - Moh Thoriq Fernanda; Trinil Susilawati; Nurul Isnaini (Faculty of Animal Science, Universitas Brawijaya, 2014)
The purpose of this study was to evaluate the implementation of Artificial Insemination using sexed frozen semen processed with percol density gradient sentrifugation method on service per conception (S/C), Non Return Rate (NRR) and Conception Rate (CR) of Ongole crossbred cattle. The material used in this study were 54 Ongole crossbred cattle which were purposively selected with criteria had conditions of estrus 2A+. Fifty five cattle were divided into 2 treatments such as P0 (non sexed semen) with Post Thawing Motility (PTM) quality 40% and P1 (sexed semen) with PTM quality 5-10%. The study was conducted in the village Boro Bunut and Boro Kemantren Pakis subdistrict Malang. The study showed that P0 (non sexed semen) had S/C 1.3, NRR0-21 74.07%, NRR22-42 74.07%, NRR43-63 74.07% and CR 74.07%, while P1 (sexed semen) had S/C 1.5, NRR0-21 74.07%, NRR22-42 59.25%, NRR43-63 59.25% and CR 55.56%. These results indicated that P0 (non-sexed semen) had better results than P1 (sexed semen), but statistically the two treatments were not significantly different (P>0.05). The highest percentage of cattle pregnancy (74.07%) was found in P0 (non sexed semen) as compared to P1 (sexed semen) which was 59.25%. Keywords: Sexing, estrus, cattle